Mercurial > hg > Members > kono > Proof > category
view system-t.agda @ 343:d8cb7f9c7980
free-monoid comment
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Fri, 18 Apr 2014 20:19:32 +0900 |
parents | 1ff7b85e5bb2 |
children | 0fb47d8ff0ed |
line wrap: on
line source
module system-t where open import Relation.Binary.PropositionalEquality record _×_ ( U : Set ) ( V : Set ) : Set where field π1 : U π2 : V <_,_> : {U V : Set} -> U -> V -> U × V < u , v > = record {π1 = u ; π2 = v } open _×_ postulate U : Set postulate V : Set postulate v : V postulate u : U f : U -> V f = \u -> v UV : Set UV = U × V uv : U × V uv = < u , v > lemma01 : π1 < u , v > ≡ u lemma01 = refl lemma02 : π2 < u , v > ≡ v lemma02 = refl lemma03 : (uv : U × V ) → < π1 uv , π2 uv > ≡ uv lemma03 uv = refl lemma04 : (λ x → f x ) u ≡ f u lemma04 = refl lemma05 : (λ x → f x ) ≡ f lemma05 = refl nn = λ (x : U ) → u n1 = λ ( x : U ) → f x data Bool : Set where T : Bool F : Bool D : { U : Set } -> U -> U -> Bool -> U D u v T = u D u v F = v data Int : Set where zero : Int S : Int → Int pred : Int -> Int pred zero = zero pred (S t) = t R : { U : Set } -> U -> ( U -> Int -> U ) -> Int -> U R u v zero = u R u v ( S t ) = v (R u v t) t null : Int -> Bool null zero = T null (S _) = F It : { T : Set } -> T -> (T -> T) -> Int -> T It u v zero = u It u v ( S t ) = v (It u v t ) R' : { T : Set } -> T -> ( T -> Int -> T ) -> Int -> T R' u v t = π1 ( It ( < u , zero > ) (λ x → < v (π1 x) (π2 x) , S (π2 x) > ) t ) sum : Int -> Int -> Int sum x y = R y ( λ z -> λ w -> S z ) x mul : Int -> Int -> Int mul x y = R zero ( λ z -> λ w -> sum y z ) x sum' : Int -> Int -> Int sum' x y = R' y ( λ z -> λ w -> S z ) x mul' : Int -> Int -> Int mul' x y = R' zero ( λ z -> λ w -> sum y z ) x fact : Int -> Int fact n = R (S zero) (λ z -> λ w -> mul (S w) z ) n fact' : Int -> Int fact' n = R' (S zero) (λ z -> λ w -> mul (S w) z ) n f3 = fact (S (S (S zero))) f3' = fact' (S (S (S zero))) lemma21 : f3 ≡ f3' lemma21 = refl lemma07 : { U : Set } -> ( u : U ) -> ( v : U -> Int -> U ) ->( t : Int ) -> (π2 (It < u , zero > (λ x → < v (π1 x) (π2 x) , S (π2 x) >) t )) ≡ t lemma07 u v zero = refl lemma07 u v (S t) = cong ( \x -> S x ) ( lemma07 u v t ) lemma06 : { U : Set } -> ( u : U ) -> ( v : U -> Int -> U ) ->( t : Int ) -> ( (R u v t) ≡ (R' u v t )) lemma06 u v zero = refl lemma06 u v (S t) = trans ( cong ( \x -> v x t ) ( lemma06 u v t ) ) ( cong ( \y -> v (R' u v t) y ) (sym ( lemma07 u v t ) ) ) lemma08 : ( n m : Int ) -> ( sum' n m ≡ sum n m ) lemma08 zero _ = refl lemma08 (S t) y = cong ( \x -> S x ) ( lemma08 t y ) lemma09 : ( n m : Int ) -> ( mul' n m ≡ mul n m ) lemma09 zero _ = refl lemma09 (S t) y = cong ( \x -> sum y x) ( lemma09 t y ) lemma10 : ( n : Int ) -> ( fact n ≡ fact n ) lemma10 zero = refl lemma10 (S t) = cong ( \x -> mul (S t) x ) ( lemma10 t ) lemma11 : ( n : Int ) -> ( fact n ≡ fact' n ) lemma11 n = lemma06 (S zero) (λ z -> λ w -> mul (S w) z ) n lemma06' : { U : Set } -> ( u : U ) -> ( v : U -> Int -> U ) ->( t : Int ) -> ( (R u v t) ≡ (R' u v t )) lemma06' u v zero = refl lemma06' u v (S t) = let open ≡-Reasoning in begin R u v (S t) ≡⟨⟩ v (R u v t) t ≡⟨ cong (\x -> v x t ) ( lemma06' u v t ) ⟩ v (R' u v t) t ≡⟨ cong (\x -> v (R' u v t) x ) ( sym ( lemma07 u v t )) ⟩ v (R' u v t) (π2 (It < u , zero > (λ x → < v (π1 x) (π2 x) , S (π2 x) >) t)) ≡⟨⟩ R' u v (S t) ∎ lemma13 : (x y : Int) -> sum x (S y) ≡ S (sum x y ) lemma13 zero y = refl lemma13 (S x) y = cong (\x -> S x ) (lemma13 x y ) lemma14sym : (x y : Int) -> sum x y ≡ sum y x lemma14sym zero zero = refl lemma14sym zero (S t) = cong (\x -> S x )( lemma14sym zero t) lemma14sym (S t) zero = cong (\x -> S x ) ( lemma14sym t zero ) lemma14sym (S t) (S t') = let open ≡-Reasoning in begin sum (S t) (S t') ≡⟨⟩ S (sum t (S t')) ≡⟨ cong ( \x -> S x ) ( lemma13 t t') ⟩ S ( S (sum t t')) ≡⟨ cong ( \x -> S (S x ) ) ( lemma14sym t t') ⟩ S ( S (sum t' t)) ≡⟨ sym ( cong ( \x -> S x ) ( lemma13 t' t)) ⟩ S (sum t' (S t)) ≡⟨⟩ R (S t) ( λ z -> λ w -> S z ) (S t') ≡⟨⟩ sum (S t') (S t) ∎ lemma16assoc : (x y z : Int) -> sum x (sum y z ) ≡ sum (sum x y) z lemma16assoc zero y z = refl lemma16assoc (S x) y z = let open ≡-Reasoning in begin sum (S x) ( sum y z ) ≡⟨⟩ S ( sum x ( sum y z ) ) ≡⟨ cong (\x -> S x ) ( lemma16assoc x y z) ⟩ S ( sum (sum x y) z ) ≡⟨⟩ sum (S ( sum x y)) z ≡⟨⟩ sum (sum (S x) y) z ∎ lemma15'' : (x y : Int) -> mul x (S y) ≡ sum x ( mul x y ) lemma15'' zero y = refl lemma15'' (S x) y = let open ≡-Reasoning in begin mul (S x) (S y) ≡⟨⟩ sum (S y) (mul x (S y)) ≡⟨⟩ S (sum y (mul x (S y) )) ≡⟨ cong (\t -> S ( sum y t )) (lemma15'' x y ) ⟩ S (sum y (sum x (mul x y))) ≡⟨ cong (\x -> S x ) ( begin sum y (sum x (mul x y)) ≡⟨ lemma16assoc y x (mul x y) ⟩ sum (sum y x) (mul x y) ≡⟨ cong (\t -> sum t (mul x y)) (lemma14sym y x ) ⟩ sum (sum x y) (mul x y) ≡⟨ sym ( lemma16assoc x y (mul x y)) ⟩ sum x (sum y (mul x y)) ∎ ) ⟩ S (sum x (sum y (mul x y) )) ≡⟨⟩ S (sum x (mul (S x) y ) ) ≡⟨⟩ sum (S x) (mul (S x) y) ∎ lemma15' : (x : Int) -> mul zero x ≡ mul x zero lemma15' zero = refl lemma15' (S x) = lemma15' x lemma15 : (x y : Int) -> mul x y ≡ mul y x lemma15 zero x = lemma15' x lemma15 (S x) y = let open ≡-Reasoning in begin mul (S x) y ≡⟨⟩ sum y (mul x y ) ≡⟨ cong ( \x -> sum y x ) (lemma15 x y ) ⟩ sum y (mul y x) ≡⟨ sym ( lemma15'' y x ) ⟩ mul y (S x) ∎ lemma15distr : (y z w : Int) -> sum (mul y z) ( mul w z ) ≡ mul (sum y w) z lemma15distr y zero w = let open ≡-Reasoning in begin sum (mul y zero) ( mul w zero ) ≡⟨ cong ( \t -> sum (mul y zero ) t ) (lemma15 w zero ) ⟩ sum (mul y zero ) ( mul zero w ) ≡⟨ cong ( \t -> sum t zero ) (lemma15 y zero ) ⟩ sum zero zero ≡⟨⟩ mul zero (sum y w) ≡⟨ lemma15 zero (sum y w) ⟩ mul (sum y w) zero ∎ lemma15distr y (S z) w = let open ≡-Reasoning in begin sum (mul y (S z)) ( mul w (S z) ) ≡⟨ cong ( \t -> sum t ( mul w (S z ))) (lemma15'' y z) ⟩ sum ( sum y ( mul y z)) ( mul w (S z) ) ≡⟨ cong ( \t -> sum ( sum y ( mul y z)) t ) (lemma15'' w z) ⟩ sum ( sum y ( mul y z)) ( sum w ( mul w z) ) ≡⟨ sym ( lemma16assoc y (mul y z ) ( sum w ( mul w z) ) ) ⟩ sum y ( sum ( mul y z) ( sum w ( mul w z) )) ≡⟨ cong ( \t -> sum y t) (lemma14sym ( mul y z) ( sum w ( mul w z) )) ⟩ sum y ( sum ( sum w ( mul w z) )( mul y z)) ≡⟨ sym ( cong ( \t -> sum y t) (lemma16assoc w (mul w z) (mul y z )) ) ⟩ sum y ( sum w (sum ( mul w z) ( mul y z)) ) ≡⟨ cong ( \t -> sum y (sum w t) ) ( lemma14sym (mul w z) (mul y z )) ⟩ sum y ( sum w (sum ( mul y z) ( mul w z)) ) ≡⟨ cong ( \t -> sum y (sum w t) ) ( lemma15distr y z w ) ⟩ sum y ( sum w (mul (sum y w) z) ) ≡⟨ lemma16assoc y w (mul (sum y w) z) ⟩ sum (sum y w) ( mul (sum y w) z ) ≡⟨ sym ( lemma15'' (sum y w) z ) ⟩ mul (sum y w) (S z) ∎ lemma15assoc : (x y z : Int) -> mul x (mul y z ) ≡ mul (mul x y) z lemma15assoc zero y z = refl lemma15assoc (S x) y z = let open ≡-Reasoning in begin mul (S x) (mul y z ) ≡⟨⟩ sum (mul y z) ( mul x ( mul y z ) ) ≡⟨ cong (\t -> sum (mul y z) t ) (lemma15assoc x y z ) ⟩ sum (mul y z) ( mul ( mul x y) z ) ≡⟨ lemma15distr y z (mul x y) ⟩ mul (sum y (mul x y)) z ≡⟨⟩ mul (mul (S x) y) z ∎